(3UMjaI GdEjeGf ef GdfjQGf aj CMhGd UGMH GdReGfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg dG JMa YXeJg HMO hdG jMUi (B... (3ebOeI(B: (3bO (B.. (3GdNHQ ef WQb GdaQjbjf aj JWGaQ HjfgeG (B... (3ceG gh hGVM Cf Gddg SHMGfg dG jNdj CQVg hdG Ndbg ef MLI JYQa HgGs
(3BNQgG (B:s
(3BNQgG(B: (3hYQafG MLJc hGQRbfG hOg hQVGg heQGabJg hQMeJg hZf de fOQc HfG CjGeg hXghQg aGLeY HjffG hHjfg hHjf GHGFg hGLOGOg aj eSJbQ QMeJc HQMeJc jG CQMe GdQGMejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs